Innovative engineering of scalable, renewable and spherical organic nanoparticles for high fire safety, UV protection and antibacterial properties of polyvinyl alcohol nanocomposites films - Nour Fathi Attia; Mohamed A. Nour; Sally E. A. Elashery (Scientific Reports)
Abstract A novel and environmentally friendly route was developed for production of sustainable flame retardant, antibacterial and UV protective nanoparticles for polymeric films nanocomposites. For the first time, dried molokhia leaves were engineered into spherical nanoparticles with an average size of 8.5 nm via an eco-friendly, one-pot solid-state ball-milling method. The engineered nanoparticles were proved using spectroscopic and microscopic techniques. The sustainable nanoparticles were employed as an efficient and green flame retardant, antibacterial and UV protective materials for polyvinyl alcohol (PVA) nanocomposite films. The distinct compatibility between PVA chains and spherical nanoparticles afford excellent homogeneous dispersion of each nanoparticle in the polymer matrix. Compared to blank PVA film which burned at a rate of 125 mm/min, the novel nanoparticles achieved significant flame retardancy for polymer nanocomposites films recording zero rate of burning. Their outstanding charring ability and naturally doped elemental composition were attributed to their higher flame retardancy achieved. Moreover, the newly developed multifunctional nanoparticles integrated outstanding UV protection feature to developed polymer nanocomposite films recording UV protection factor superiority of more than 900% compared to nanoparticle free film. Noteworthy to note that, the nanoparticles afford excellent inhibition to bacterial growth against Escherichia coli and Staphylococcus aureus over the surface of developed polymer nanocomposite films achieving clear inhibition zone of 9 and 7.6 mm compared to zero mm for pristine polymer film, respectively. In addition, a proposed and clarified flame retardancy mechanism was presented. Additionally, an assessment was conducted regarding the economic feasibility of producing sustainable multifunctional nanoparticles on an industrial scale.